The Costs of Urban Sprawl - Infrastructure and Transportation - Trubka, Roman; Newman, Peter; Bilsborough, D. (Royal Australian Institute of Architects, 2010)
This is one of three companion papers taken from a study that assesses the comparative costs of urban redevelopment with the costs of greenfield development. This paper shows that substantial costs could be saved in infrastructure and transport if urban redevelopment became the focus. The second paper GEN 83: The Costs of Urban Sprawl - Predicting Transport Greenhouse Gases from Urban Form Parameters assesses how these different urban typologies perform with respect to greenhouse gases. The third paper GEN 85: The Costs of Urban Sprawl - Physical Activity Links to Healthcare Costs and Productivity discusses the health costs and productivity losses that can be linked to human inactivity in suburban living. The savings in transport and infrastructure for 1000 dwellings are in the order of $86 million up-front for infrastructure and $250 million for annualised transportation costs over 50 years.